100 поделок из ненужных материалов - Цамуталина Елена Евгеньевна (Умелые руки, 2002)
Экземпляры: ф.2 (2003) / Инвентарный номер: 46902 / Цена: / Сис.шифр: 37.2 / Авт.знак: Ц 15 / ГРНТИ: 75.35 / ББК: 37.248